2004
DOI: 10.1086/425301
|View full text |Cite
|
Sign up to set email alerts
|

Test Particle Energization by Current Sheets and Nonuniform Fields in Magnetohydrodynamic Turbulence

Abstract: We perform numerical experiments of test particle energization in turbulent magnetic and electric fields obtained from pseudospectral direct numerical solutions of compressible three-dimensional magnetohydrodynamic (MHD) equations with a strong background magnetic field. The natural tendency of turbulent MHD fields is to form current sheets along the magnetic field direction, as well as strong nonuniform fields in the transverse directions. By associating the MHD dissipation length scale with the ion inertial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
260
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(275 citation statements)
references
References 44 publications
11
260
1
Order By: Relevance
“…Overall, this behavior is similar to the "proton" case in Ref. [26], where a ten times stronger mean field resulted in much faster acceleration. Consequently test particles in our simulations stay well below the maximum energy derived in that reference.…”
supporting
confidence: 83%
“…Overall, this behavior is similar to the "proton" case in Ref. [26], where a ten times stronger mean field resulted in much faster acceleration. Consequently test particles in our simulations stay well below the maximum energy derived in that reference.…”
supporting
confidence: 83%
“…In previous papers describing particle acceleration, it has been seen that the particles undergo repeated acceleration and deacceleration as they pass through the turbulent magnetic field domain (Dmitruk et al 2004;Dmitruk & Matthaeus 2006;Turkmani et al 2006). In this experiment we assume that a single coherent current sheet is more likely to only provide one single acceleration of the particles, at least for the ones that very rapidly reach the domain boundaries.…”
Section: Individual Acceleration Patternsmentioning
confidence: 96%
“…Mostly these have consisted of situations representing MHD turbulence (Dmitruk et al 2003(Dmitruk et al , 2004Dmitruk & Matthaeus 2006;Turkmani et al 2006) finding the accelerated particles to reach high velocities, having power law distributions with steep power indexes (Turkmani et al 2006). The typical result is that the fastest particles reach energies much higher than found in solar observations.…”
Section: Particle Setupmentioning
confidence: 99%
“…Diffusive acceleration of particles by MHD waves was contrasted and compared to direct E-fields and shocks formed by large scale current sheets in the break-up model. Several recent articles showed that the non linear evolution of the MHD waves form small scale structures, which act also as shocks or UCS [23,22,24].…”
Section: The Loop Modelmentioning
confidence: 99%